How to Keep Sustainable Development Between Enterprises and Employees? Evaluating the Impact of Person–Organization Fit and Person–Job Fit on Innovative Behavior - Yuan Tang; Yuan Tang; Yun-Fei Shao; Yi-Jun Chen; Yin Ma (Frontiers in Psychology, 2021)
High-tech industries often regard workers as their main source of value creation. In order to stimulate their employees' willingness to innovate and their innovative behavior and reduce the turnover intention, companies are now seeking to establish employer–employee relationships in which their employee's willingness to stay is not simply driven by extrinsic motivations. Therefore, it is an important topic in human resources for companies to implement measures that encourage employees to willingly devote themselves to their jobs and consider organizational growth as a component of their career development. This study aimed to investigate the effect of person–organization fit and person–job fit on employees' innovative behavior and turnover intention via the mediators including job satisfaction and organizational commitment. Six hundred ninety-seven employees from China's eight major high-tech industries were examined in this study, and the empirical results were analyzed using partial least squares. Based on the results, it is suggested that the person–organization fit and person–job fit are both crucial factors affecting employees' job satisfaction and organizational commitment, which, in turn, increase employees' willingness to innovate in their jobs and reduce their turnover intentions. Furthermore, this study could serve as a reference for companies in selecting employees, promoting job satisfaction, and developing strategies for sustainable development.